Cancer stem cell markers ALDH1 and Bmi1 expression in oral erythroplakia revisited: Implication for driving the process of field cancerization. (5th September 2019) - Feng, Jinqiu; Zhou, Zengtong; Shi, Linjun; Yang, Xi; Liu, Wei
Abstract: The correlation of ALDH1 and Bmi1 expression in potentially malignant oral erythroplakia (OE) with oral carcinoma development was reported in our earlier study. Interestingly, a model of field cancerization orchestrated by the cancer stem cells (CSC) was proposed and suggested the identification of CSC‐specific markers is useful for prognosis and providing novel targets for prevention and treatment of field cancerization. We revisited the correlation of ALDH1 and Bmi1 expression in OE with the second and multiple carcinomas development. Strikingly, we observed that the expression of ALDH1 and Bmi1 within a single potentially malignant OE lesion significantly correlate with subsequently developing multiple and multifocal carcinomas, which parallels the process of oral field cancerization. Significantly, ALDH1 and Bmi1 are well‐defined markers of CSC for head and neck cancer. Consequently, we provided a preliminary evidence for CSC driving the process of field cancerization.